To find the height of a tree that is 64 inches tall in its pot, we need to use the given information to determine the relationship between the height in the pot (x) and the height without the pot (y).
Looking at the given data, we can observe that the height without the pot (y) is always 12 inches less than the height in the pot (x).
Therefore, to find the height without the pot (y) when the height in the pot (x) is 64 inches, we subtract 12 from 64.
Height without pot = Height in pot - 12
Height without pot = 64 - 12
Height without pot = 52 inches
So, the height of the tree without the pot is 52 inches.
@bot
The table shows the heights in inches of trees after they
have been planted. What is the height of a tree that is 64 in.
tall in its pot?
Height in pot, x Height Without Pot, y
30 18
36 24
42 30
48 36
3 answers
Determine which ordered pair is a solution of y=8x
To determine which ordered pair is a solution of the equation y = 8x, we need to substitute the given values of x and y into the equation and check if the equation holds true.
The given ordered pairs are:
1) (3, 24)
2) (5, 40)
3) (6, 48)
Let's substitute the values from the first ordered pair (3, 24) into the equation:
y = 8x
24 = 8(3)
24 = 24
The equation holds true for the first ordered pair.
Now, let's substitute the values from the second ordered pair (5, 40) into the equation:
y = 8x
40 = 8(5)
40 = 40
The equation holds true for the second ordered pair as well.
Lastly, let's substitute the values from the third ordered pair (6, 48) into the equation:
y = 8x
48 = 8(6)
48 = 48
The equation holds true for the third ordered pair as well.
Thus, all three ordered pairs (3, 24), (5, 40), and (6, 48) are solutions of the equation y = 8x.
The given ordered pairs are:
1) (3, 24)
2) (5, 40)
3) (6, 48)
Let's substitute the values from the first ordered pair (3, 24) into the equation:
y = 8x
24 = 8(3)
24 = 24
The equation holds true for the first ordered pair.
Now, let's substitute the values from the second ordered pair (5, 40) into the equation:
y = 8x
40 = 8(5)
40 = 40
The equation holds true for the second ordered pair as well.
Lastly, let's substitute the values from the third ordered pair (6, 48) into the equation:
y = 8x
48 = 8(6)
48 = 48
The equation holds true for the third ordered pair as well.
Thus, all three ordered pairs (3, 24), (5, 40), and (6, 48) are solutions of the equation y = 8x.